What constitute a variation in construction from legal perspective - Lim, Cheng Sim (2007)
Construction projects are complex thus the requirement for changes to be made before they are completed is inevitable. Construction contracts commonly include variations clauses to enable the employer’s design team to vary the design and specification. Various forms of construction contract defined the variation differently and different standard forms of contract have different wordings for it. The variation clauses are usually drafted in very wide terms and appeared to be all embracing. Although the descriptions are clear but it is difficult to determine the point where it is ‘variation’ or ‘new work’, and it is not clear from the ambit of these clauses as to how extensive a variation may be and still be binding. Thus variation clauses often give rise to argument, debate and litigation. The main objective of this study is to determine what constitute a variation in construction from legal perspective. The scopes of this study are (1) contractual provisions in the three major and popular forms of construction contract in Malaysia, namely PAM 98 Form, PWD Form 203A (Rev. 10/83) and CIDB 2000, and (2) Legal cases reported in Lexis Nexis in relation to variations in Malaysia and other Commonwealth countries. The research methodology adopted for this report consists of 4 stages. Stage 1: initial study and finding the research topic, objective, scope and outline; Stage 2: collecting data and research design; Stage 3: analyzing and interpreting data and Stage 4: writing-up. This report covers five (5) chapters. Chapter 1 sets the background of the study, problem statement, objective of the study, scope and limitation of the study, research methodology and the organization of the chapters. Chapter 2 discusses some basic terminologies and provides a general understanding of variation, contractual terms and contract interpretation on variation. Chapter 3 examines the detailed provision of variation clauses in relation to ‘definition of variation’ and ‘valuation of variation’ of the most commonly used local standard forms, i.e. PAM 98 Form, PWD 203A (Rev. 10/83) and CIDB Form 2000. Chapter 4 analyses legal perspective of ‘what constitute a variation’ in construction of the various court cases chosen in order to achieve the objective of this project report. Chapter 5 summarises the findings of the research according to the research objective. The finding derived from the analysis of the court cases is that there is no single legal perspective regarding what constitute a variation in construction. However, based on the cases analysed, the most common issue is whether the extra over of the changes fall under reasonable scope and nature of the original work; but what is reasonable under the circumstances will be a matter for the courts to establish on the facts of the particular case.